Repetitive transcranial magnetic stimulation decreased effortful frontal activity for shifting in patients with major depressive disorder. Issue 11 (27th June 2022) - Shirakawa, Yuka; Yamazaki, Ryuichi; Kita, Yosuke; Kitamura, Yuzuki; Okumura, Yasuko; Inoue, Yuki; Matsuda, Yuki; Kodaka, Fumitoshi; Shigeta, Masahiro; Kito, Shinsuke
Abstract : Patients with major depressive disorder (MDD) exhibit several clinical symptoms including difficulties in flexible thinking. Flexible thinking mainly relies on a cognitive ability called shifting; however, the mechanisms underlying shifting in patients with MDD have not yet been clarified. Therefore, we conducted a preliminary intervention study to clarify the association between depression and shifting ability. We examined the hemodynamic responses in the frontal regions during the shifting task using functional near-infrared spectroscopy (fNIRS) in 21 patients with MDD who were treated using high-frequency repetitive transcranial magnetic stimulation (rTMS). Behavioral performance on the shifting task did not change between pre- and posttreatments, whereas patients who responded well to rTMS treatment showed a significant decrease in hemodynamic responses posttreatment. On the other hand, the poor responders did not show significant changes in the hemodynamic responses between pre- and posttreatments. These results suggest that the good responders were successfully remedied with rTMS treatment and did not need effortful activity in frontal regions for shifting, which made their brain activity more efficient.